Genomic analysis of Streptococcus canis from different hosts in Italy 2004–2021: diversity, antimicrobial resistance, and virulence profiles - Cucco, Lucilla; Albini, Elisa; Blasi, Francesca; Orsini, Serenella; Fiorucci, Alessandro; Dettori, Annalisa; Petrin, Sara; Peruzzo, Arianna; Salaris, Silvano; Paniccià, Marta; Pezzotti, Giovanni; Massacci, Francesca Romana; et al. (Frontiers in Veterinary Science, 2025)
Streptococcus canis, a multi-host pathogen commonly isolated from dogs and cats has been occasionally reported in severe cases of human infection. This study aimed to explore the genetic diversity, antimicrobial resistance (AMR), and pathogenicity of S. canis isolates collected between 2004–2021, in Italy. Fifty-five S. canis isolates from clinical cases in domestic animals were investigated for susceptibility to antibiotics and then characterized for sequence type (ST), virulence profile, and antimicrobial-resistant genes through whole genome sequencing (WGS). All isolates were susceptible to beta-lactams, while frequently exhibiting resistance to lincosamides, chlortetracyclines, and macrolides. Six out of 55 isolates of S. canis, all collected between 2020 and 2021, were multi-drug resistant (MDR). The most common AMR gene in the dataset was lmrP conferring resistance for streptogramin, tetracycline, macrolide, streptogramin A, and lincosamide. Other determinants of AMR were the tet genes. Twenty-one distinct STs were identified, with ST9 being the most prevalent in our collection. Regarding the virulence genes, forty-three isolates were positive for the ssp-5 gene, which encodes an agglutinin receptor. Comparison with other 46 S. canis genomes available in public repositories revealed that the Italian isolates clustered by the S. canis M-like (SCM) protein gene and ST and did not group according to their host, area, or year of origin. In conclusion, our study underscores the susceptibility of Italian S. canis isolates to beta-lactam antibiotics, which remain the first line of defense in managing infections. In Italy, ST9 represents the predominant clone of this pathogen. Despite the diversity in species of origin and the various STs identified, our findings confirm that S. canis has not adapted to different ecological niches and corroborate the accidental pathogenic nature of human cases.